2006
DOI: 10.1038/nature05200
|View full text |Cite
|
Sign up to set email alerts
|

Complex zeolite structure solved by combining powder diffraction and electron microscopy

Abstract: Many industrially important materials, ranging from ceramics to catalysts to pharmaceuticals, are polycrystalline and cannot be grown as single crystals. This means that non-conventional methods of structure analysis must be applied to obtain the structural information that is fundamental to the understanding of the properties of these materials. Electron microscopy might appear to be a natural approach, but only relatively simple structures have been solved by this route. Powder diffraction is another obvious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
160
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 202 publications
(165 citation statements)
references
References 23 publications
3
160
0
2
Order By: Relevance
“…Rietveld refinement of this model revealed that additional symmetry was present in the structure. That is, atomic positions related by a center of symmetry (not present in C2cm) were found to be insignificantly different from one another, so the structure Electron crystallography and powder diffraction [39]. The insets show the corresponding SAED pattern (left), the contrast-transfer-function corrected and symmetry-averaged image, from which the phases were calculated (middle), and the computer simulation from the structural data (right).…”
Section: Im-5mentioning
confidence: 99%
See 1 more Smart Citation
“…Rietveld refinement of this model revealed that additional symmetry was present in the structure. That is, atomic positions related by a center of symmetry (not present in C2cm) were found to be insignificantly different from one another, so the structure Electron crystallography and powder diffraction [39]. The insets show the corresponding SAED pattern (left), the contrast-transfer-function corrected and symmetry-averaged image, from which the phases were calculated (middle), and the computer simulation from the structural data (right).…”
Section: Im-5mentioning
confidence: 99%
“…A further option is to use an approximate or partial model that has been deduced from HRTEM images as a seed for generating starting phase sets. Different combinations of these options eventually led to the determination of the three most complex zeolite structures known (TNU-9 [39], IM-5 [40] and SSZ-74 [41]). The relevant aspects of these structure solutions are given in the following sections to illustrate the procedure.…”
Section: Combining X-ray Powder Diffraction Data With Hrtem Imagesmentioning
confidence: 99%
“…Electron crystallography has several important advantages in structure analysis of these materials; single crystal electron diffraction can be collected from micro-and nano-sized crystals and high resolution transmission electron microscopy (HRTEM) images can be obtained, from which crystallographic structure factor phase information can be extracted [2]. During the past years, several of the most complicated zeolite structures were solved by electron crystallography alone [3,4] or together with PXRD [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…along [100], [010] and [001]. Recently, several zeolites with unit cell dimensions in the range 14-57 A have been solved by combining electron crystallography and powder X-ray diffraction (Gramm et al, 2006, Baerlocher et al 2007). These are the most complicated zeolites ever solved by crystallography (including X-ray crystallography).…”
Section: Introductionmentioning
confidence: 99%